RANCANGAN TEMPAT DAN GEROBAK SAMPAH UNTUK PERBAIKAN SISTEM PENGUMPULAN SAMPAH DI TAMAN HUTAN RAYA (TAHURA) IR. H. DJUANDA - Nawangpalupi, Catharina Badra; Pambudi, Noorhan Firdaus (Universitas Muhammadiyah Surakarta, 2015)
Tahura Juanda (Tahura) is a forest park located between the city of Bandung, West Bandung Regency and Regency Bandung. It has a role to preserve the city environment. Â Number of visitors in Tahura made the Tahura need to have a good waste management system. Â Optimal waste management system can be achieved, if garbage collection and removal equipment work well, such is the place and garbage carts. Based on observation, the condition of the premises and garbage carts are less good. Therefore, it is needed to redesign the place and garbage carts through the whole process of product development. The study was conducted by identifying the needs of the janitor, Tahura management staff, and visitors. Identifications produce seven types of trash and five types garbage carts requirements, which will be the basis in developing the concept. The process of developing the concept of trash and garbage carts done using a combination tables and SCAMPER process. All concepts are selected by screening matrix concept and assessment concepts, to pick the concept of trash and garbage cart.